Delik Perkosaan terhadap Perempuan dalam Perspektif Hukum Hindu - Anak Agung Made Angga Harta Yana; I Nyoman Gede Sugiartha; I Nyoman Subamia (Warmadewa Press, 2022)
The crime of rape is a form of crime that when charged is like depriving and destroying the highest throne that is very precious, namely the virginity of a woman. Although the problem of the crime of rape has been regulated normatively in the Criminal Code, in fact the protection of rape victims cannot be said to be a good legal umbrella. Hindu law also considers that rape is a major sin called Dratikrama. In this regard, How is the Regulation of Rape In The Study of Criminal Law And Hindu Law? And How is the Effectiveness of the Application of Criminal Sanctions to Rape Offenses in the Study of criminal Law and Hindu Law?. This research uses a normative type of research. The regulation of the Rape of Women is contained in the Criminal Code (KUHP) in Articles 285 – 289 and in the Compendium of Hindu Law (Manava Dharmasastra). The application of rape sanctions against women in the criminal law is still not effective to impose because there are still irregularities in the sanctions and in hindu law it has not been effective because it is caused by several factors.